PERSEPSI PEGAWAI TERHADAP PERILAKU BERMAIN JUDI ONLINE DI LEMBAGA PEMBINAAN KHUSUS ANAK BANDUNG - Fikri, Muhammad Aufa; Rusmana, M.Si , Dr. Aep; Yaneri, S. ST, M. Kesos. , Ahmad (Politeknik Kesejahteraan Sosial Bandung, 2025)
This study examines perceptions of online gambling behavior at the Special Juvenile Correctional Institution (LPKA) Bandung city. The background of this study is based on the increasing exposure of adolescents to online gambling as a result of easy digital access and weak cognitive control. This study used a descriptive qualitative method with the main theories of System 1 and System 2 (Kahneman), cognitive biases, the framing effect, and prospect theory to understand the dynamics of the informans’ perceptions toward online gambling activities. Data was collected through in-depth interviews and documentary studies, with informants selected using a purposive sampling technique. Data validity was tested through triangulation of sources and techniques. The findings indicated that the perceptions of juvenile offenders were more dominated by fast thinking (System 1) and reinforced by cognitive biases and the framing effect, which presented misleading promotional narratives. Meanwhile, slow ability (System 2) had not been optimal yet in processing risks. The tendency to make decisions based on high potential gains despite the risk of loss, as explained in prospect theory, further reinforced vulnerability to speculative behavior. As an intervention, this study proposes the “SADAR DIGITAL” program as an educational approach to enhance risk awareness, emotional control, and digital literacy. This program is expected to serve as a preventive model in the context of child development and protection in the digital age.